2017
DOI: 10.2134/cftm2016.06.0048
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Evaluation of Annual and Perennial Cool‐Season Forage Systems for Stocker Production in the Lower Transition Zone

Abstract: Cool-season forages provide high-quality forage throughout the cooler months, which can reduce winter feed and hay consumption by extending the grazing season in the Southeast. Limited research has been conducted to simultaneously evaluate common annual and perennial cool-season forage options during this time period. A 2-year grazing trial was conducted to evaluate annual ryegrass (Lolium multiflorum L.), mixtures of cereal rye (Secale cereal L.) and annual ryegrass, and novel endophyte tall fescue [Lolium ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The grazing of WC can also lead to greater milk production when compared to red clover and grasses (Johansen et al., 2017). Meanwhile, cereal rye can extend the grazing season and, when mixed with legumes, can generate an average daily gain (ADG) equal to that from pastures without legumes and with 45–67 kg ha −1 of added synthetic N fertilizer (Mckee et al., 2017). In addition, the consumption of LM species, such as cereal rye, can provide sufficient forage very early in the growing season, because it is the most cold‐hardy of all forages, with ADG greater than 0.8 kg day −1 (Mckee et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The grazing of WC can also lead to greater milk production when compared to red clover and grasses (Johansen et al., 2017). Meanwhile, cereal rye can extend the grazing season and, when mixed with legumes, can generate an average daily gain (ADG) equal to that from pastures without legumes and with 45–67 kg ha −1 of added synthetic N fertilizer (Mckee et al., 2017). In addition, the consumption of LM species, such as cereal rye, can provide sufficient forage very early in the growing season, because it is the most cold‐hardy of all forages, with ADG greater than 0.8 kg day −1 (Mckee et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, cereal rye can extend the grazing season and, when mixed with legumes, can generate an average daily gain (ADG) equal to that from pastures without legumes and with 45–67 kg ha −1 of added synthetic N fertilizer (Mckee et al., 2017). In addition, the consumption of LM species, such as cereal rye, can provide sufficient forage very early in the growing season, because it is the most cold‐hardy of all forages, with ADG greater than 0.8 kg day −1 (Mckee et al., 2017). Therefore, there is a need to determine the benefits of grazing and corn production in LM production systems.…”
Section: Introductionmentioning
confidence: 99%
“…In the southeastern United States, cool‐season forage crops are utilized as the primary feedstuffs for stocker cattle ( Bos spp. ; Beck et al., 2008; Gunter et al., 2012) and winter‐feeding systems for beef cattle production (McKee et al., 2017). Examples of cool‐season annual forage crops include grasses (cereal rye [ Secale cereale L.] and oats [ Avena sativa L.]), legumes (crimson [ Trifolium incarnatum L.] and arrowleaf clover [ T. vesiculosum Savi]), and forbs (radish [ Raphanus sativus L.] and rape [ Brassica napus L.]).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found grazing to be more profitable than feeding hay (Adams et al., 1994; Schoonmaker et al., 2003). In addition, grazing cool‐season perennial grasses versus cool‐season annual grasses can be more profitable for beef cattle production (Beck et al., 2008; Islam et al., 2011; McKee et al., 2017). Perennial systems that cover the soil also reduce soil erosion and provide other environmental benefits versus annual systems (Karlen et al., 2006).…”
Section: Introductionmentioning
confidence: 99%